The development and validation of Nurse Managers' competencies in Indonesia - Pertiwi, Ariani Arista (Thesis -- (Master of Arts in Nursing (Nursing Administration)) -- University of the Philippines Manila)
Competence is considered as one big contributor to a nurse manager's success (McCarthy & Fitzpatrick, 2009). Unavailability of standard in competency may provoke role confusion and career development obscrutiny. Indonesian career ladder for nurses has established since 2006, but there is no specific competencies standard yet especially for the nurse managers. This study aimed to determine the nurse managers' competencies in three levels; first level (Nurse Managers II), middle level (Nurse Managers III), and top level (Nurse Managers IV) in Indonesia. This study also aimed to validate the competencies of nurse managers II derived from FGD and from the panel of experts with the use of factor analysis and to compare the nurse managers' competencies determined by the Indonesian Nurse Managers Association (HPMI).
Mixed methods research design was utilized in this study; with focus group discussion was held in the first phase to determine the nurse managers competencies according to nurse managers in clinical practice. A review by a panel of experts then carried out to give comments and suggestions to the list of competencies from FGD's result as the second phase. Content analysis was conducted to analyze the FGD and panel of expert review result. In the third phase of the study, the NM II were asked to fill up a 5-likert scale self assessment instrument on their competencies. A factor analysis was done to validate the construct of the nurse managers' competencies. The reliability of the instrument was test using the Cronbach-a reliability test.
There were 49 competencies statements for the first level (Nurse Managers II), 36 competencies statements for the middle level (Nurse Managers III), and 60 competencies statements for the top level (Nurse Managers IV) from the panel of experts review. There were 7 components of nurse managers' competencies for NM II as suggested by factor analysis result. The nurse managers' competencies resulted in this research have similarities and differences with the established standard of competencies and the draft by the Indonesian Nurse Managers Association.
Keywords: Nurse Manager; Competency